Jean-Luc Marion: Pengantar atas ‘Keterberian’ dan ‘Fenomen yang Melimpah’ - Tandyanto, Yulius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2014)
For some contemporary thinkers, traditional and modern metaphysical systems were not considered as an adequate account, for they might have abolished the ontological difference. Such circumstances might have taken place because metaphysics was thought of as circumscribing by considering the whatness of any phenomena in form of, or oder of, the same, i.e. substance, essence or first cause. Jean-Luc Marion moves further and suggests phenomenological accounts that culminate in the givenness and the saturated phenomenon – ideas which open the possibilites to overcome the inadequacy of metaphysics. With the phenomenological third reduction, Marion shows that givenness already presents itself which is anterior to the dichotomy between essence and existence. This phenomenology of givenness enables phenomena to appear by itself in the saturated phenomena. In a paradoxical way, he shows that the constituting subject had already been constituted. Phenomenology, therefore, allows the subject to describe any phenomena in the form of, or order of, the other such as Marion proposed. Considering the contexts, this article may serve as an introduction to the notion of givenness and the saturated phenomenon.